Fast leave-one-out methods for inference, model selection, and diagnostic checking. (December 2020) - Belotti, Federico; Peracchi, Franco
In this article, we describejackknife2, a new prefix command for jackknifing linear estimators. It takes full advantage of the available leave-one-out formula, thereby allowing for substantial reduction in computing time. Of special note is thatjackknife2 allows the user to compute cross-validation and diagnostic measures that are currently not available afterivregress 2sls, xtreg, andxtivregress .